Are we training psychiatrists to develop skills in intellectual disability psychiatry?: current European context and future directions - Dias, Marisa Casanova; Perera, Bhathika; Riese, Florian; Picker, Livia De; Costa, Mariana Pinto da; Petricean, Alina; Kanellopoulos, Athanasios; Krysta, Krzysztof; Baessler, Franziska (European psychiatry, 2020)
The majority of people with intellectual disabilities (ID) and psychiatric disorders access mainstream mental health services across Europe. However, only 56% of countries provide postgraduate psychiatric training in ID according to a survey across 42 European countries. We explore the challenges of ID training and make recommendations for education and health policymakers.
Gesehen am 27.01.2021